Whose transformation is this?: Unpacking the ‘apparatus of capture’ in Sweden's bioeconomy - Holmgren, Sara; Giurca, Alexandru; Johansson, Johanna; Kanarp, Christoffer Söderlund; Stenius, Tove; Fischer, Klara (Environmental innovation and societal transitions, 2022)
This study investigates how and by whom the Swedish (forest) bioeconomy has been shaped so far. We unpack emerging bioeconomies as discursive constructs and use the ‘apparatus of capture’ as a conceptual framework to understand and rethink the Swedish bioeconomy. Based on analysis of empirical data from multiple sources (e.g., online surveys, in-depth interviews, participatory observations), we identify a closed bioeconomy network structure that includes forest industries, major forest owner associations, regional councils and research institutes/universities. The network (re)produces three key storylines that appeal to the majority of parties in the national parliament, defines the boundaries of relevant expertise, and discredits environmental regulation and expertise. Through these storylines the Swedish bioeconomy is turned into an issue of innovation governance, which blurs the boundaries between public and private interests in forests. To counteract future capture, different types of knowledges and forest perspectives need further exploration in Swedish bioeconomy and forest governance.